ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN FARMASI PT. INDOFARMA, Tbk TAHUN 2011 – 2018 - Abdurrahman, Abdurrahman; Munandar, Aris (MOTIVASI, 2020)
This study aimsto determine the effect of the pharmaceutical companies PT. indofarma Tbk year 2011 – 2018 by using financial ratios. The type of research used in this study is descriptive and the research method used is quantitative because there are numbers and calculations using formulas. Data analysis techniques use financial statement analysis, which consist of liquidity ratios, solvency ratios, profitability ratios and activity ratios. Based on the analysis of liquidity ratios that effect financial performance measured by the current ratio that does not meet the standard this show the company is not safe in the short term. Solvency ratios that affect financial performance are measured by debt ratios that are above the industry standard and are said to be good, indicating that the company is able to manage assets well and reduce funding by using debt. Profitability ratios that affect financial performance are measured by net profit margins where the ratio does not meet industry standards due to losses experienced by the company in the period 2016 - 2018 caused by competition from similar companies. The ratio of activities that affect financial performance measured by total asset turnover shows the company's revenue from sales is not maximal and does not meet industry standards.